Learning by arguing. (October 2019) - Iordanou, Kalypso; Kuhn, Deanna; Matos, Flora; Shi, Yuchen; Hemberger, Laura
Abstract: Can argumentation practice simultaneously promote knowledge acquisition while advancing skill in the practice itself? We examine the effectiveness of a dialog-based argument curriculum in fostering middle-school students' knowledge acquisition as well as dialogic and written argumentation skill with respect to a content-rich, socially significant topic. Results of two studies, one involving a physical science topic and the other a social topic, showed a single intervention could meet both objectives, Study 1 following a previously used model of extended intervention (nine sessions over five weeks) and Study 2 experimenting with a dense model of six intervention hours completed over two days. Both were found effective. A novel question-and-answer method was found superior to a traditional one in promoting acquisition of factual knowledge sufficient to support argumentation. With respect to skill gains, a prompt to consider incongruent evidence showed the greatest effect in furthering mastery of a critical argument skill – to acknowledge and address, rather than ignore, evidence that counters one's favored position. Highlights: An argument curriculum can be effective in fostering both knowledge and skill goals. Rather than a traditional text, information was acquired via a Q&A method. The Q&A condition yielded better use of evidence to support claims in final essay. Dense engagement (six hours completed over two days) proved effective. A prompt to consider incongruent evidence enhanced attention to it.